Automotive Cut-off Sanding Device for Single Locomotive Emergency Braking - JIA Ya-min; CHEN Bo; LI Hao-qin (机车电传动)
To solve the serious problem of automatic block district track circuit bad shunting caused by massive sanding in single locomotive emergency stop and locomotive occupying block district with no display, which caused frequently rear-end collision accident, automotive cut-off sanding device in single locomotive emergency braking was developed. Design function of the device was verified and advanced by overall static and dynamic test.